(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study evaluates the customer satisfaction towards the service quality of selected stalls at Bestlink College of the Philippines in terms of tangible, reliability, responsiveness, and assurance; the significant relationship between and among the service quality and its customer satisfaction in terms of aforecited variables; issues do people have with the selected stalls that they can complain about in terms of their customer service; and proposed recommendations to address the following concerns in attaining the service quality on customer satisfaction. The results of this study reveal that the evaluation of customer satisfaction with the service quality of selected stalls is evaluated as strongly agreed upon in terms of tangible, reliability, responsiveness, and assurance; the issue with the food stalls in terms of customer service is that no availability of seats. This study recommended that to prevent customers from getting fed up with the food they buy and to ensure that the food they serve is fresh rather than just reheated, sell freshly cooked and nutritious one to attract a lot of customers. This action will help the stalls to maintain and give the best of what customers want and make them satisfied.